(untitled) (Computer systems and information technologies, 2023)
The current challenge is to provide automatic decision support in a smart home. A study of the top solutions of well-known smart homes has shown that existing solutions usually do not provide for fully automatic control in a smart home, but are focused either on automatic control in conjunction with manual control or user-controlled control. Therefore, the goal of this study is to support decision-making for fully automatic temperature control in a smart home. Human well-being and performance depend on the meteorological conditions of the environment in which a person is located. The most important condition for high performance, rest, and health is the creation and maintenance of an optimal home microclimate. One of the main parameters of the indoor microclimate is temperature. The room temperature control subsystem ensures the optimal temperature level and allows for individual adjustment for each family member. The developed rules for determining the optimal room temperature allow you to evaluate the existing temperature parameters for further automatic operation of the smart home temperature control subsystem in residential premises of various types. The purpose of the temperature control subsystem is to provide comfortable conditions in residential premises of various types in terms of their temperature regime. The developed decision-making method for temperature control in a smart home, which is the basis of the smart home temperature control subsystem, provides a comfortable and optimal (taking into account building and sanitary and hygienic standards) temperature in the corresponding living space. The results of the functioning of the smart home temperature control decision-making method have shown that the developed method provides for the recognition of situations (optimal temperature, low temperature, high temperature) and support for decision-making on the temperature regime in a certain type of residential space (turning on heating devices, turning on cooling devices, no action, etc.).